Effectiveness of Pronate-Supinate Pipe in Sub-Acute Stroke Patients: A Randomized Controlled Trial - Prodbumrung, Jirawan; Srisoparb, Waroonapa; Sangrahy, Suvinai (Srinagarind Medical Journal, 2022)
Background and Objective: Muscle weakness is the main cause of upper limb functional activity (ULFA) limitation post-stroke. This study aimed to develop a piece of novel equipment, the pronate-supinate pipe, to improve upper limb muscle strength and to investigate the effectiveness of the pronate-supinate pipe Method: A randomized controlled clinical sixteen sub-acute stroke patients were randomly allocated to experimental (n=8) and control groups(n=8). Both groups received a 45-minute conventional physical therapy program 3-day / week for 4 weeks. The experimental group received a strength training program for pronator and supinator muscles using the pronate-supinate pipe 15 times/ set for 3 sets with a 2-minute rest interval at each set for 30 minutes before the conventional physical therapy. The primary outcome was ULFA as measured by the Streamlined Wolf Motor Function Test for sub-acute stroke patients (SWMFT-Sub-acute). The secondary outcomes were pronate/ supinate active range of motion (AROM), grip muscle strength and upper limb motor recovery as measured by a goniometer, hand grip dynamometer and the Fugl-Meyer assessment for upper extremity (FMA-UE) respectively. Measurements were conducted at baseline and post-intervention. Results: The result of this study showed that ULFA, pronate/ supinate AROM, grip strength and upper limb motor recovery of the experimental group at post-intervention improved from baseline significantly (p<0.05) but did not differ from the control group. Conclusions: The pronate supinate pipe training has a superior effect on ULFA than the conventional physical therapy alone.